Towards cost-effective drug discovery: Reusable immobilized enzymes for neurological disease research - Andrys, Rudolf; Monnier, Charline; Antonijević Miljaković, Evica; Mickova, Veronika; Musilek, Kamil; Zemanova, Lucie (Talanta, 2024)
Enzyme handling and utilization bears many challenges such as their limited stability, intolerance of organic solvents, high cost, or inability to reuse. Most of these limitations can be overcome by enzyme immobilization on the surface of solid support. In this work, the recombinant form of human cholinesterases and monoamine oxidases as important drug targets for neurological diseases were immobilized on the surface of magnetic non-porous microparticles by a non-covalent bond utilizing the interaction between a His-tag terminus on the recombinant enzymes and cobalt (Co2+) ions immobilized on the magnetic microparticles. This type of binding led to targeted enzyme orientation, which completely preserved the catalytic activity and allowed high reproducibility of immobilization. In comparison with free enzymes, the immobilized enzymes showed exceptional stability in time and the possibility of repeated use. Relevant Km, Vmax, and IC50 values using known inhibitors were obtained using particular immobilized enzymes. Such immobilized enzymes on magnetic particles could serve as an excellent tool for a sustainable approach in the early stage of drug discovery.
Keywords: enzymy imobilizované; Immobilization; monoaminoxidasa; Humans; Nervous System Diseases; kobalt; Monoamine Oxidase; lidé; Recombinant Proteins; Cobalt; rekombinantní proteiny; acetylcholinesterasa; objevování léků; Cholinesterases; Enzyme Stability; Monoamine oxidases; analýza nákladů a výnosů; Acetylcholinesterase; Sustainability; nemoci nervového systému; Magnetic microparticles; Neurological disorders; Drug Discovery; Cost-Benefit Analysis; Enzymes, Immobilized; stabilita enzymů